Discussion of “Experimental Study on Unconfined Compressive Strength of Rubberized Cemented Soil” by Jie He, Duanwei Guo, Dexin Song, Fangcheng Liu, Lei Zhang, and Qifeng Wen - He, Jie; Guo, Duanwei; Song, Dexin; Liu, Fangcheng; Zhang, Lei; Wen, Qifeng; Taiba, Abdellah Cherif; Mahmoudi, Youcef; Belkhatir, Mostefa (KSCE journal of civil engineering, 2024)
This paper aims to provide further elaboration on the main subject discussed in the recently published article titled “Experimental Study on Unconfined Compressive Strength of Rubberized Cemented Soil” in the KSCE Journal of Civil Engineering, authored by He et al. (2023). The intention here is to enhance the overall cohesion of the paper and render it more conducive to meaningful discussion.